Arab Contributions to Introducing the Roman Territories During the Byzantine and the Seljuk Periods - Al Rawadieh , Al Mahdi (Dirasat: Human and Social Sciences, 2022)
This article aims to show to which extent the Arab and Muslim historians and geographers are aware of and familiar with the Byzantine empire’s territories (Roman territories), and their information about its administrative and military divisions in the first eight Hijri centuries (8-14 AD), which is the period in which the Roman territories were under Byzantine rule, and later by Seljuk who dominated these territories after the Battle of Manzikert in 463 AH / 1071 AD, and before its submission to Ottoman rule. The study also explores the main routes used by Arabs and Muslims in their military campaigns to invade the Roman territories, and the routes used by Christian pilgrims in the area between the Levant and Constantinople (Istanbul). The study is based on the old traditional Arabic Sources until the eighth century AH / fourteenth century AD, and it shows how Arab historians and geographers dealt with the names of Byzantine places and the Arabization of these names.